A10.05 Optimising existing tools for reaching an adequate disease control in patients with spondylarthritis. (24th February 2016) - Deaconu, C; Opriş, D; Peltea, A; Mazilu, D; Borangiu, A; Groșeanu, L; Negru, M; Constantinescu, C; Săulescu, I; Bojincă, V; Vlad, V; Bălănescu, A; et al.
Abstract : Background and objectives: Disease activity in spondylarthritis (SpA) is widely evaluated through disease activity scores such as BASDAI, ASDAS and PtGA, with no proven superiority between them. The aim of this study was to subdivide patients with anti-TNF therapy according to their disease status indicated by scores in order to evaluate group characteristics with further assessment on the quality of each activity indicator. Materials and methods: We included 100 SpA patients under anti-TNF therapy (32 infliximab, 33 adalimumab, 35 etanercept). We collected demographic, clinical (BASDAI, ASDAS, PtGA) and laboratory (ESR, CRP) data. Statistical analysis was performed with SPSS 20.0. Results: We evaluated disease activity for the entire study group based on conventional scores: BASDAI, ASDAS-CRP, ASDAS-ESR, acute phase reactants and PtGA. When used as an external criterion PtGA showed that 12% of patients had active disease while 88% were classified as low disease activity (PtGA < 5). Mean ASDAS-CRP/ESR in the active group were 3.39/3.24. Mean BASDAI score in the high activity group was 5.66. We showed that both ASDAS scores had good discriminating capacities, with similar values when using the SMD (ASDAS-CRP and ASDAS-ESR – SMD 2.00). In our study group, based on PtGA, BASDAI outperformed ASDAS scores with a SMD of 3.33. We used ROC curves of the disease activity scores by using the PtGA ≥ 5 as variable of high disease activity state. For ASDAS-CRP, ASDAS-ESR and BASDAI the AUCs ( area under curve ) were 0.89 (P = 0.05), 0.88 (P < 0.001), and 0.99 (P = 0.009), respectively. For CRP and ESR the AUCs were 0.81 and 0.79 (P = 0.001, P = 0.003). This shows the high accuracy of the three scores in assessing SpA activity. When dividing patients according to BASDAI score (4 as cut-off), 14% showed a more active disease than the rest of 86% who had low disease activity. Mean ASDAS scores in the first group were 3.31 and 3.16, respectively. BASDAI correlated to both ASDAS scores (r = 0.65 and 0.71, P < 0.001) and PtGA stronger to BASDAI(r = 0.912, P < 0.01) than ASDAS(r = 0.67 and 0.71, P < 0.01). Conclusion: We proved that disease activity scores have good discriminatory power and that BASDAI and ASDAS perform similarly in assessing and investigating SpA patients. BASDAI outperformed ASDAS when using PtGA as criterion.